Mechanisms That Underly T Cell Immunity in Graves’ Orbitopathy - Fang, Sijie; Lu, Yi; Huang, Yazhuo; Zhou, Huifang; Fan, Xianqun (Frontiers in Endocrinology, 2021)
Graves’ orbitopathy (GO), also known as thyroid-associated ophthalmopathy, is the most common ocular abnormality of Graves’ disease. It is a disfiguring, invalidating, and potentially blinding orbital disease mediated by an interlocking and complicated immune network. Self-reactive T cells directly against thyroid-stimulating hormone receptor-bearing orbital fibroblasts contribute to autoimmune inflammation and tissue remodeling in GO orbital connective tissues. To date, T helper (Th) 1 (cytotoxic leaning) and Th2 (antibody leaning) cell subsets and an emerging role of Th17 (fibrotic leaning) cells have been implicated in GO pathogenesis. The potential feedback loops between orbital native residential CD34- fibroblasts, CD34+ infiltrating fibrocytes, and effector T cells may affect the T cell subset bias and the skewed pattern of cytokine production in the orbit, thereby determining the outcomes of GO autoimmune reactions. Characterization of the T cell subsets that drive GO and the cytokines they express may significantly advance our understanding of GO and the development of promising therapeutic strategies against pathological T cells.